Between Code and Treatise: The Hard Challenge of the Restatement of Copyright - Liu, Joseph P. (The Columbia Journal of Law & the Arts, 2021)
The proposed Restatement of Copyright raises a question that has been obvious to everyone from the very start of the project: How do you restate an area of the law governed by a comprehensive federal statute? Restatements have, to date, focused near-exclusively on common law subjects. The Reporters of other Restatements thus did not operate in the shadow of an authoritative uniform federal statute. Instead, they faced an unruly and “ever-growing mass of decisions in the many different jurisdictions, state and federal, within the United States.” From this mass of decisions, the Reporters derived the “black-letter law” and “restated” the law in a form resembling a code. In doing so, reporters sought to bring order, clarity, and coherence to a body of law that lacked any other means of doing so. But if this act of restating the law in the form of a code is a central feature of a Restatement, then how do you restate an area of law that already has a comprehensive code? What is to be gained by essentially re-codifying the law?